The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/geront/45.suppl_1.96
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Stress, and Satisfaction of Staff Who Care for Residents With Dementia

Abstract: Attending to the welfare and ongoing training of workers who have demonstrated job commitment may lessen their tendency to become jaded over time or seek job opportunities elsewhere. Further, the attitudes the staff hold related to dementia and the training they receive to provide dementia care are important for their own well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
238
3
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(270 citation statements)
references
References 18 publications
25
238
3
4
Order By: Relevance
“…The EQ-5D index is scored from -0.59 to 1 (worst health state to full health), and the EQ-5D VAS is scored from 0 to 100 (worst imaginable health state to best imaginable health state), so the staff in this study had reasonable health at baseline (Table 16). Staff attitudes to dementia were consistent with those reported by qualified nurses working in nursing homes in one UK study, 139 higher than a pilot study in care homes 162 and also more positive than those reported from a large US study, 163 where the mean total score of direct care staff on the ADQ was 70.7 (SD 6.4), compared with our mean score of 75.16 (SD 7.04).…”
Section: Staff Descriptivessupporting
confidence: 87%
“…The EQ-5D index is scored from -0.59 to 1 (worst health state to full health), and the EQ-5D VAS is scored from 0 to 100 (worst imaginable health state to best imaginable health state), so the staff in this study had reasonable health at baseline (Table 16). Staff attitudes to dementia were consistent with those reported by qualified nurses working in nursing homes in one UK study, 139 higher than a pilot study in care homes 162 and also more positive than those reported from a large US study, 163 where the mean total score of direct care staff on the ADQ was 70.7 (SD 6.4), compared with our mean score of 75.16 (SD 7.04).…”
Section: Staff Descriptivessupporting
confidence: 87%
“…5 Scores range from 0 to 10. Zero is no cognitive impairment (for purposes of comparison, the comparable Mini-Mental State Examination [MMSE] scores are greater than 23), 1-2 is mild impairment (MMSE, 19-23), 3-5 is moderate impairment (MMSE,(12)(13)(14)(15)(16)(17)(18), and 6-10 is severe impairment (MMSE, less than 12).…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Some have argued that training increases job satisfaction and possibly reduces turnover [30]. All groups underscored that education which taught them what dementia is like from the resident's perspective was critical.…”
Section: Discussionmentioning
confidence: 99%